"When Is Short, Sweet?" Selection Uncertainty and Online Review Presentations. Issue 2 (3rd April 2017) - Church, E. Mitchell; Iyer, Lakshmi
ABSTRACT: Online customer reviews are an important part of e-commerce product selection. When used effectively, online reviews may reduce the uncertainty inherent in making product selection decisions online, but how best to deal with thousands of online customer reviews? Past research considers online review summarization, where reviews are reduced to numeric ratings, key phrases, keywords or product characteristics. However, in their original form, online reviews contain the carefully crafted narratives of past customers, elements of which may not be amenable to summarization. In this research, we present findings of a laboratory experiment which examines the impact of review summarization when evaluating different types of products online. Key findings include evidence that perceptions of product selection uncertainty depend on online review presentation format and the category of the product under consideration. Additionally, the study provides evidence that the e-commerce retailers may benefit from varying online review presentations across specific types of products.